Antioxidant and Antimicrobial Activity of Porcine Liver Hydrolysate in Meat Emulsion and Their Influence on Physico‐Chemical and Color Deterioration During Refrigeration Storage. Issue 7 (19th June 2019) - Verma, Akhilesh K.; Chatli, Manish Kumar; Kumar, Pavan; Mehta, Nitin
Abstract : Abstract: Present study explored the quality changes in meat emulsion during storage at refrigerated temperature prepared with inclusion of three different levels of liver protein hydrolysate (LPH) in meat emulsion (LPH‐1: 0.03, LPH‐2: 0.06, and LPH‐3: 0.09%) and compared with control (LPH: 0.00%) and positive control (butylated hydroxytoluene: 0.02% w/w meat emulsion). Physico‐chemicals, antioxidant activities, lipid oxidation, color profile, microbial quality, and microbial challenge test (MCT) were assessed for all groups. Results indicated that all evaluated attributes were considerably improved with increase in LPH concentration. Among treated groups, LPH‐3 was maintained comparatively better for every attribute assessed during storage studying. Regarding microbial quality, LPH‐3 showed ( P ≤ 0.05) lower aerobic plate count, coliforms, and yeast mold counts than others. Likewise for MCT, significantly ( P ≤ 0.05) lower microbial counts were recorded in LPH‐3 during storage. Results concluded that LPH can be a good alternative substance for the preservation of meat for lower oxidation activity and bacterial growth. Practical Application: Meat emulsion is more prone to lipid oxidation and microbial contamination than fresh meat. However, for the preparation of convenient, value added meat products, better utilization of freezed meat and reduced cooking time have enhanced the demand of emulsion‐based meat products. Liver protein hydrolysate can be a good alternative substance for the preservation of emulsion‐based meat products. Treated groups better retained their physico‐chemical properties, color indices, and showed lower oxidation and microbial counts than control. It can be exploited commercially for the preparation of functional foods, nutraceuticals, and cosmeceuticals.